Forecast of Socio-Economic Consequences of SARS-CoV-2 Infection and the COVID-19 Pandemic - Mabiala, Gilbert; Sukhareva , Irina A.; Voloshin , Aleksei I.; Toropova , Irina S. (Economy of Regions, 2024)
The global spread of SARS-CoV-2, the cause of COVID-19, remains a public health issue. The pandemic has resulted in approximately 563,312,528 instances of infection, endangering health and increasing the risk of unemployment and income loss for many people worldwide. The article presents a computational and graphical analysis of the effects (shocks) of SARS-CoV-2 and new variants of COVID-19 on human activity, simulates the caused socio-economic damage and forecasts the society’s socio-economic development. To this end, cases of infection, mortality and recovery in the population were analysed, forecast scenarios for the trajectory of socio-economic indicators affected by new variants of COVID-19 were substantiated. The study applied the economic and statistical method, as well as the tabular and graphical approaches to the assessment of empirical data. Analysis of the proposed quantitative model for examining the impact of the COVID-19 infection revealed the reasons for the decline in commercial activity, socio-economic stagnation and a worldwide economic recession. The pandemic-related measures have exacerbated the pre-2019 crisis, resulting in unprecedented socio-economic upheavals, an increase in global poverty from 17.1 % to 25.9 %, and an estimated damage to the world economy of more than 1,976.80 trillion roubles. Additionally, the rate of socio-economic well-being recovery have slowed from 11.8 to 6.7 months. The healthcare system will face significant challenges if the share of actively infected persons exceeds 1 %. Moreover, the 10 % infection rate will cause the malfunctioning of socio-economic infrastructure components of the world economy accompanied by macroeconomic shocks, as well as a persistent decrease in gross domestic product by 2.4 % in 2021–2022 and 4 % in 2023. This situation can exacerbate already-existing socio-economic contradictions, raise unemployment and inflation, lead to a fall in the population’s real income.